LAWSONIA INERMIS LINNAEUS: A PHYTOPHARMACOLOGICAL REVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Lawsonia inermis L. is a much branched glabrous shrub or small tree, cultivated for its leaves although stem bark, roots, flowers and seeds have also been used in traditional medicine. The plant is reported to contain carbohydrates, proteins, flavonoids, tannins and phenolic compounds, alkaloids, terpenoids, quinones, coumarins, xanthones and fatty acids. The plant has been reported to have analgesic, hypoglycemic, hepatoprotective, immunostimulant, anti-inflammatory, antibacterial, antimicrobial, antifungal, antiviral, antiparasitic, antitrypanosomal, antidermatophytic, antioxidant, antifertility, tuberculostatic and anticancer properties. It is now considered as a valuable source of unique natural products for development of medicines against various diseases and also for the development of industrial products. This review gives a bird’s eye view mainly on the pharmacognostic characteristics, traditional uses, phytochemistry and pharmacological actions of the plant.